Association of dietary quality indicators with gallstones in the US: NHANES 2017–2020 - Weigen Wu; Yuchen Pei; Junlong Wang; Qizhi Liang; Wei Chen (BMC Public Health)
Abstract Background While dietary factors are known to influence gallstone development, the specific relationships between comprehensive dietary quality indicators and gallstone risk remain poorly understood. This study aimed to explore the association between dietary quality indicators and gallstones using data from the 2017 to 2020 US National Health and Nutrition Examination Survey (NHANES). Methods A total of 6,623 US adults were extracted from the 2017–2020 NHANES, of which 734 participants self-reported having gallstones. Dietary quality indicators were assessed using 24-hour dietary recall data. We used multivariate logistic regression analysis to evaluate the association between dietary quality indicators and the likelihood of gallstones. To delineate the non-linear relationships and threshold effects, we utilized a restricted cubic spline (RCS) regression model. Subgroup analyses were also performed. Results After adjusting for sex, age, race, education, poverty-to-income ratio, body mass index, large weight loss, alcohol use, smoking, physical activity, diabetes, hypertension, heart failure, coronary heart disease, angina pectoris, heart attack, total calories, total cholesterol, estrogen use, antihyperglycemic drug use, statin use, and glucocorticosteroid use (Model 4), a higher Dietary Inflammatory Index (DII) and lower Alternative Healthy Eating Index (AHEI), Healthy Eating Index (HEI-2020), Dietary Approaches to Stop Hypertension (DASH), and Mediterranean Diet (MED) were all significantly associated with gallstones. Further RCS analysis revealed a nonlinear relationship between the DII and gallstones, with a threshold value of 1.842. Above this threshold, for each unit increase in the DII score, the odds of developing gallstones increased by 27.5%. Subgroup analysis demonstrated that this association was consistent across all subgroups. Conclusion Participants with gallstones exhibited poor dietary habits. Adopting a diet that reduces inflammation and supports overall health may help lower the risk of gallstone development, with potential implications for dietary recommendations in clinical practice.